A paradigm shift in food safety for Africa - Ayalew, Amare; Kareem, Fatima Olanike; Grace, Delia (AKADEMIYA2063, 2023)
Food safety systems globally, and more so in Africa, have not kept pace with the complexity of food safety challenges. In Africa, these challenges include, inter alia, fragmented food safety management and mandate, and poor investment and budgetary finances on sanitary and phytosanitary (SPS)related quality infrastructures (Jaffee and Henson 2004; Czubala, Shepherd, and Wilson 2009; PAQI 2020). The challenges are further aggravated by the poor food safety culture in the continent. These challenges of unsafe food have undermined the pace and state of food system transformation in the continent. This is because unsafe foods adversely impact public health but also thwart efforts at boosting trade in food and agricultural commodities and reduce agricultural trade (Jaffee et al. 2019; Kareem, Martínez-Zarzoso, and Brümmer 2022), thereby leading to loss of earnings and income (Kareem, Martínez-Zarzoso, and Brümmer 2022; Kareem and Martínez-Zarzoso 2020). In addition, unsafe food undermines the potential and actual gains in improving food security and nutrition.